1984
DOI: 10.1039/c39840000471
|View full text |Cite
|
Sign up to set email alerts
|

Matrix photolysis of [(η5-C5H5)W(CO)2NO]: an intramolecular formation of an isocyanate ligand

Abstract: Matrix isolation evidence from [ ( T ~-C ~H ~) W ( C O ) ~N O ]( l a ) and its labelled analogues containing 13CO, ( 2 8 0 , or N180indicates an intramolecular CO attack at the nitrogen of a NO ligand in the photochemical formation of a group 6 metal isocyanato-species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…In some cases these products may be preceded by a η 2 ‐XY species with conversion to the insertion product being either thermally or photochemically initiated. In an examination of the photochemistry of CpW(CO) 2 NO (Cp=η 5 ‐C 5 H 5 ) in frozen gas matrices, Rest and co‐workers found evidence for intramolecular formation of an isocyanate ligand to give CpW(CO)(NCO), presumably through the reaction of CO with a photochemically generated nitrene intermediate; the ultimate fate of the O‐atom of the nitrosyl ligand remains elusive 14. In a solution photolysis study of the closely related CpMo(CO) 2 NO in the presence of an excess of PPh 3 , McPhail and co‐workers found that in addition to the simple PPh 3 substitution product, generation of PPh 3 O, CpMo(CO) 2 (NCO)PPh 3 , and CpMo(CO)(NCO)(PPh 3 ) 2 were also observed, providing evidence for intramolecular activation of the nitrosyl ligand to give an unobserved nitrene intermediate 15.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases these products may be preceded by a η 2 ‐XY species with conversion to the insertion product being either thermally or photochemically initiated. In an examination of the photochemistry of CpW(CO) 2 NO (Cp=η 5 ‐C 5 H 5 ) in frozen gas matrices, Rest and co‐workers found evidence for intramolecular formation of an isocyanate ligand to give CpW(CO)(NCO), presumably through the reaction of CO with a photochemically generated nitrene intermediate; the ultimate fate of the O‐atom of the nitrosyl ligand remains elusive 14. In a solution photolysis study of the closely related CpMo(CO) 2 NO in the presence of an excess of PPh 3 , McPhail and co‐workers found that in addition to the simple PPh 3 substitution product, generation of PPh 3 O, CpMo(CO) 2 (NCO)PPh 3 , and CpMo(CO)(NCO)(PPh 3 ) 2 were also observed, providing evidence for intramolecular activation of the nitrosyl ligand to give an unobserved nitrene intermediate 15.…”
Section: Methodsmentioning
confidence: 99%
“…593 ' 594 Carbonyl loss is the primary photoprocess on photolysis of [Cr(CO) 2 (NO)Cp] either in a matrix or in solution, 595 though for the tungsten analogue formation o f an isocyanate species by intramolecular attack of CO on NO can also be observed. 596 In coordinating solvents, useful solvent-stabilized intermediates can be prepared photochemically and then used in subsequent reactions, for example 598 ' 5^ Phosphine substitution in [W(CO) 2 (NO)Cp] with PMe 3 occurs rapidly at room temperature by an associative mechanism; in neat PMe 3 the ring-slipped complex [W(C0) 2 -(NO)(PMe 3 ) 2 (r| 1 -C 5 H 5 )] can be isolated. 600 The CO ligands in [M(CO) 2 (NO)Cp] are also susceptible to nucleophilic attack, for example by ylids or by organolithium reagents.…”
Section: [M(co) 2 (No)cp] and Related Compoundsmentioning
confidence: 97%
“…In photochemical reactions of carbonylnitrosyl complexes, the formation of isocyanate can be attributed to a nitrido or nitrene intermediate, which adds carbon monoxide [26, 27] [Scheme , Equation (8)]. Formation of isocyanato complexes was observed by irradiation of [CpW(CO) 2 NO] 27 and of [CpMo(CO)(PPh 3 )(NO)] 26. From matrix isolation experiments with isotopic labeling of CO and NO in [CpW(CO) 2 NO] clear evidence could be obtained that isocyanate is formed by intramolecular migration of CO to a nitrene species 27.…”
Section: Reaction Of Carbonyl Metal Complexes With the Azide Ionmentioning
confidence: 99%
“…Formation of isocyanato complexes was observed by irradiation of [CpW(CO) 2 NO] 27 and of [CpMo(CO)(PPh 3 )(NO)] 26. From matrix isolation experiments with isotopic labeling of CO and NO in [CpW(CO) 2 NO] clear evidence could be obtained that isocyanate is formed by intramolecular migration of CO to a nitrene species 27. Vice versa, the migration of CO from an NCO ligand to the metal atom to form a ruthenium nitride cluster was also reported [Scheme , Equation (9) and Equation (10)].…”
Section: Reaction Of Carbonyl Metal Complexes With the Azide Ionmentioning
confidence: 99%